Dialogue (Academy of Management Review, 2002)
Commentary is presented for a number of past articles from the “Academy of Management Review.” They include “The business-level RBV: Great Wall or Berlin Wall?” bay R. L. Priem, published in a 2001 issue, “Is the resource-based “view” a useful perspective for strategic management research?” by R. L. Priem and J. E. Butler, published in a 2001 issue and “Tautology in the resource-based view and the implications of externally determined resource value: Further comments,” by J. E. Butler and R. L. Priem, published in a 2001 issue.